Action video game play and transfer of navigation and spatial cognition skills in adolescents who are blind - Connors, Erin; Chrastil, Elizabeth; Sanchez, Jaimie; Merabet, Lotfi B. (Frontiers in Human Neuroscience, 2014)
For individuals who are blind, navigating independently in an unfamiliar environment represents a considerable challenge. Inspired from recent developments in accessible technology and the rising popularity of video games, we have developed a novel approach to train navigation and spatial cognition skills in adolescents who are blind. Audio-based Environment Simulator (AbES) is a software application that allows for the virtual exploration of an existing building set in an action video game metaphor. We investigated the ability and efficacy of adolescents with early onset blindness to acquire spatial information gained from the exploration of a virtual indoor environment using this ludic approach to learning. Following game play, participants were then assessed on their ability to transfer and mentally manipulate acquired spatial information in a set of navigation tasks carried out in the real environment represented in the game. The transfer of navigation skill performance was markedly high suggesting that interacting with AbES leads to the generation of an accurate spatial mental representation. Furthermore, there was a positive correlation between success in game play and navigation task performance. The role of virtual environments and gaming in the development of mental spatial representations is also discussed. We conclude that this novel software and learning by a gaming approach can facilitate the transfer of spatial knowledge and can be used by individuals who are blind for the purposes of navigation in real-world environments.